Multimodal Imaging in Birdshot Retinochoroiditis. (3rd September 2017) - Pohlmann, Dominika; Macedo, Sergio; Stübiger, Nicole; Pleyer, Uwe; Joussen, Antonia M.; Winterhalter, Sibylle
ABSTRACT: Purpose: To describe retinal vascular changes in Birdshot Retinochoroiditis (BSRC) with multimodal imaging techniques and functional values. Methods: In this single-center study, 64 eyes of 32 subjects with BSRC were classified according to disease activity and duration and underwent imaging with spectral domain optical coherence tomography, fluorescein angiography, indocyanine green angiography, fundus autofluorescence, and optical coherence tomography angiography (OCTA). Results: Mean age of the patients was 60 years (range, 38–74). OCTA revealed capillary loops (58%), telangiectatic vessels (44%), increased intercapillary spaces (52%), altered vascular architecture (53%), and rarefication of C-scans (63%) in retinal layers. Increased rarefications of C-scans ( p  = 0.0056; p  = 0.0046) and altered vascular architecture ( p  = 0.0120; p  = 0.0243) in superficial and deep capillary layers were significantly correlated with disease activity. Conclusion: OCTA adds new insights in a multimodal imaging approach of retinal vascular layer visualization in BSRC and may contribute to existing methods for diagnosing severity and potentially progression of the disease.